Low‐frequency waves within isolated magnetic clouds and complex structures: STEREO observations. Issue 4 (6th April 2015) - Siu‐Tapia, A.; Blanco‐Cano, X.; Kajdic, P.; Aguilar‐Rodriguez, E.; Russell, C. T.; Jian, L. K.; Luhmann, J. G.
Abstract Complex Structures (CSs) formed by the interaction of magnetic cloud (MC)‐like structures with other transients (e.g., another MC, a stream interaction region, or a fast stream of solar wind) were frequently observed in the interplanetary space by STEREO spacecraft during the solar minimum 23 and the rising phase of the solar cycle 24. Here we report the presence of low‐frequency waves (LFWs) inside some isolated MCs (IMCs) and inside the CSs observed by STEREO during such period (2007–2011). It is important to study in detail the properties of waves in space plasmas since particle distribution functions can be modified by wave‐particle interactions. We compare wave characteristics within IMCs with those waves observed inside CSs. Both left‐handed (LH) and right‐handed (RH), near‐circularly polarized, transverse and almost parallel‐propagating LFWs (around the proton cyclotron frequency) were sporadically observed inside both IMCs and CSs. In contrast, compressive mirror‐mode waves (MMs) were observed only within CSs. We studied local plasma conditions inside the IMCs and CSs to gain insight about wave origin: most of the MMs within CSs were observed in regions with enhanced plasma beta (β>1); the majority of the LH waves were found in low beta plasmas (β<1), and the RH waves were predominantly observed at moderate betas (0.4<β≤2). These observations are in agreement with linear kinetic theory predictions for the growth of the mirror, the LH ion cyclotron, and the RH ion firehose instability, respectively. It is possible that the waves were generated locally inside the IMCs and CSs via temperature anisotropies. The plasma beta enhancements that were frequently observed inside the CSs may be the result of compressions and heating taking place inside the interacting structures.